Assessment of Differential Global Positioning System (DGPS Technology for Generating Accurate Topographic Maps and Controls: A Case Study of Farin-Lamba to Kwali College Area - Victor Fredrick; Dahiru Mohammed Zakari; Vandu Umaru Lazarus; Victor Markus; Issa Suleiman Ola; Bila Nwandari Adiel; Victoria Asabe Ahmed; Suliat Adebayo; Abdulrahman Muhammad; Yikwot Monica Ghinsel (International Journal of Land, 2025)
This study investigates the application of Differential Global Positioning System (DGPS) for topographic mapping and control point establishment in Farin-Lamba to Kwali College Area. The second order Survey controls extension are critical indices for ensuring structural and border control mechanisms in environmental development projects. However, creating these controls using traditional ways presents major obstacles. Most modern techniques are improvements on ancient approaches, which raises the possibility of environmental dangers and security issues due to faulty boundary demarcations, right of ways, sewage lines, and poor design plan execution. Differential Global Positioning System (DGPS) technology has emerged as a ground-breaking solution, effectively addressing these challenges with precision and efficiency within defined time frames. This study utilized Network Adjustment methods, using Trimble GNSS receiver Trimble (R8) in static mode observation, to capture data for establishing second-order controls in the study area. The data were collected, processed and adjusted using Trimble Business Centre Version 3.40 software. The map of the second order Controls were generated using ArcGIS software, and the accuracies were rigorously assessed, with triangulation networks meeting the required standards within a 99% confidence level. The implementation of DGPS techniques further enhanced precision through systematic error correction in second-order control densification. Advanced DGPS calibration techniques employed through ensuring unparalleled accuracy in surveying and mapping applications. The developed control points are versatile for research, student practical, property surveys, and numerous engineering projects in addition to meeting the required accuracy standards. The findings demonstrate that DGPS technology is capable of producing precise control points and topographic maps. According to the study, DGPS technology should be used for topographic mapping and the development of control points in comparable regions.
Keywords: Production of Controls and Topographic Map; global positioning system (GPS)